ANALYSIS THE IMPACT OF COVID-19 ON PASSENGER SERVICES - Satya Bramasta, Hanugrah; Sudrajat, Sudrajat; Rinaldi, Ridho (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
In 2019, the Bamboo Curtain country was shocked by the news that a 55- year-old citizen from Wuhan, Hubei Province, was infected with the virus. Presumably this is the first case that happened. The disease caused by the virus is called wuhan pneumonia which is then called by the World Health Organization (WHO) Coronavirus Disease 19 (Covid 19). The Covid-19 pandemic has also impacted many industries, especially in the air transportation sector. Many changes with increasingly stringent requirements and stricter supervision from officers and passengers to comply with health protocols to prevent the spread of Covid-19. The impact of this virus is very influential in passenger services where there are changes and differences in services during a pandemic and after a pandemic where from the terminal entrance service to the waiting room or departure terminal area and there are points where service changes are implemented. Inside the terminal, passengers will experience a significant difference in service to prevent the spread of the virus, from wearing masks at the airport terminal, providing touchless technology at the terminal and providing free hand sanitizer facilities to maintain the health and comfort of passengers. Related data and information are used to carry out a qualitative descriptive analysis in this study. This description can be used to explain in general the events that occurred related to the impact of the Covid-19 pandemic on changes in passenger service. The purpose of this research is to produce recommendations to add to existing and new policies regarding departure terminal facilities while still prioritizing preventing the spread of Covid-19.